Portrait of the Artist as Hermes A Study of Myth and Psychology in Thomas Mann's Felix Krull - Nelson, Donald F. (UNC Studies in the Germanic Languages and Literatures, 1971)
Within the framework of Jungian archetypal psychology and utilizing Karl Kerényi's theories on Hermes and the archetypal symbolism of mother and daughter, this book combines the mythopoeic and psychoanalytical approaches in interpreting Krull's development as both a mythic identification with Hermes and an odyssey into the archaic depths of the Collective Unconscious. As a counterpart to the thematic line of investigation, detailed stylistic analyses aim at pointing out significant correspondences between form and content.